2023
DOI: 10.1007/s40615-023-01555-z
|View full text |Cite
|
Sign up to set email alerts
|

Examining Racial/Ethnic Differences in Patterns of Opioid Prescribing: Results from an Urban Safety-Net Healthcare System

Abstract: Prescription opioids still account for a large proportion of overdose deaths and contribute to opioid use dependence (OUD). Studies earlier in the epidemic suggest clinicians were less likely to prescribe opioids to racial/ethnic minorities. As OUDrelated deaths have increased disproportionately amongst minority populations, it is essential to understand racial/ethnic differences in opioid prescribing patterns to inform culturally sensitive mitigation efforts. The purpose of this study is to estimate racial/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Another study conducted at a safety net hospital demonstrated that White patients were in the 95th percentile of receiving opioid prescriptions compared to racial-ethnic minorities [19]. The study also noted that White patients were more likely to experience an opioid use disorder subsequent to an opioid prescription compared to minority patients.…”
Section: Discussionmentioning
confidence: 95%
“…Another study conducted at a safety net hospital demonstrated that White patients were in the 95th percentile of receiving opioid prescriptions compared to racial-ethnic minorities [19]. The study also noted that White patients were more likely to experience an opioid use disorder subsequent to an opioid prescription compared to minority patients.…”
Section: Discussionmentioning
confidence: 95%
“…We also found that Black patients are at an increased risk for a short‐acting opioid prescription. Whereas, other studies have found decreased opioid prescribing in the Black patients 61,63,64 . Recently, a study of Medicare claims data found that a lower mean annual dose of opioids for Black patients compared to white 65 .…”
Section: Discussionmentioning
confidence: 96%
“…Whereas, other studies have found decreased opioid prescribing in the Black patients. 61,63,64 Recently, a study of Medicare claims data found that a lower mean annual dose of opioids for Black patients compared to white. 65 This current finding may be due to our evaluation of shortacting opioids alone or our definition of opioids, as well as our chosen study-specific variables.…”
Section: Short-acting Opioid Prescriptionmentioning
confidence: 99%
“…We attempted to characterize cognitive behavioral therapies, but low prevalence limited further assessment by race and ethnicity. Fourth, differential OUD diagnosis by practitioners based on beneficiaries’ racial demographics may contribute to under- or overestimation of the differences in PT or chiropractic care for Black or African American and Hispanic persons, as these groups historically have been underdiagnosed for OUD . Fifth, a limitation inherent with administrative claims data is that we could not capture self-paid services for which Medicare did not provide reimbursement, leading to possible underestimation of chronic pain services among beneficiaries.…”
Section: Discussionmentioning
confidence: 99%